2015
DOI: 10.14737/journal.aavs/2015/3.1.40.57
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicology: A Review of Pesticides Induced Toxicity in Fish

Abstract: | Throughout the world pesticides are widely employed in agriculture sector in order to elevate crops' yield with low labour and efforts. Pesticides exposure leads to toxicity in many non-target organisms, fish being one of the most prominent among these. Most of the time acute concentration of these pesticides leads to mortality while sub lethal concentration of these pesticides result in different lethal changes. These changes may be in behaviour of the exposed fish such as change in feeding behaviour, attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 104 publications
(91 reference statements)
0
34
0
3
Order By: Relevance
“…Mallatt (1985) stated that gill lesions can be divided into two groups, one that reflects the direct effect of toxicants and another corresponding to defense responses of fishes. Several studies have been demonstrated on laboratory experiments, to determine the toxicity of heavy metals, organochlorine pesticides, and petroleum hydrocarbon products to fish gill (Al-Attar 2007; Garcia- Santos et al 2007;Patnaik et al 2011;Santos et al 2011;Hesni et al 2011;Moitra et al 2012;Ullah and Zorriehzahra 2015). Hyperplasia and lamellar fusion known to be induced by many gill tissue irritants; however, focal points of cellular hypertrophy and necrosis followed by epithelial rupture reflect the direct deleterious effects of heavy metals in fish gills (Mazon et al 2002).…”
Section: Histological Observation On the Livermentioning
confidence: 99%
“…Mallatt (1985) stated that gill lesions can be divided into two groups, one that reflects the direct effect of toxicants and another corresponding to defense responses of fishes. Several studies have been demonstrated on laboratory experiments, to determine the toxicity of heavy metals, organochlorine pesticides, and petroleum hydrocarbon products to fish gill (Al-Attar 2007; Garcia- Santos et al 2007;Patnaik et al 2011;Santos et al 2011;Hesni et al 2011;Moitra et al 2012;Ullah and Zorriehzahra 2015). Hyperplasia and lamellar fusion known to be induced by many gill tissue irritants; however, focal points of cellular hypertrophy and necrosis followed by epithelial rupture reflect the direct deleterious effects of heavy metals in fish gills (Mazon et al 2002).…”
Section: Histological Observation On the Livermentioning
confidence: 99%
“…Esos compuestos ingresan inicialmente a las plantaciones y, debido a que los canales de riego están en contacto directo con los ríos, terminan finalmente llegando a los causes principales como el Río Grande en Turbo -Antioquia. Entre los principales mecanismos de acción asociados a la exposición a agroquímicos se encuentran daños en genes, proteínas, alteraciones enzimáticas, cambios en la replicación del ADN y alteraciones que llevan a mutaciones (Çavaş & Könen, 2007;Murthy et al, 2013;Ullah & Zorriehzahra, 2015). Estos últimos mecanismos están implicados en los efectos clastogénicos observados en eritrocitos de peces, como B. henni, expuestos a estos agentes.…”
Section: Fig 2 Frecuencia Media De Emn En Ejemplares Deunclassified
“…Esta actividad se desarrolla en forma intensiva principalmente debido al cultivo de banano y plátano que constituyen el primer producto agrícola de la región (Mintrabajo, 2013;Zamora & García-Valencia, 2007). Estos monocultivos demandan la aplicación aérea de agroquímicos, especialmente del herbicida glifosato y del insecticida clorpirifos, cuya presencia ha sido detectada en las fuentes hídricas de esta región (CORPOURABA, 2007;INVEMAR, 2004;Vivas-Aguas et al, 2011;Bonilla, Peinado, Urdaneta, & Carrascal 2000) y sus efectos genotóxicos han sido reportados en una gran variedad de organismos (Çavaş & Könen, 2007;Cavas, 2011;Giesy, Dobson, & Solomon, 2000;Gollapudi, Mendrala, & Linscombe, 1995;Murthy, Kiran, & Venkateshwarlu, 2013;Nwani et al, 2010Nwani et al, , 2011Rahman, Mahboob, Danadevi, Banu, & Grover, 2002;Ruiz & Marzin, 1997;Ullah & Zorriehzahra, 2015). Adicionalmente, la contaminación de aguas superficiales con estas sustancias se da como resultado de procesos de escurrimientos pluviales y lixiviación (Polard et al, 2011a), los cuales se ven favorecidos en esta zona por una continua precipitación.…”
unclassified
“…Heavy metals accumulate in the food chain, and adversely affect fish. Consequently, it sometimes leads to mass mortality [10] or alters the physiology and biochemical aspects of the fish [11]. On account of its economic worth and public health value, research regarding heavy metal contents in fish tissues has been carried out in different parts of the world as well as Pakistan [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%